Thermochronological record of Middle–Late Jurassic magmatic reheating to Eocene rift-related rapid cooling in the SE South China Block - Tao, N.; Li, Zheng-Xiang; Danisik, Martin; Evans, Noreen; Batt, G.; Li, W.; Pang, C.; Jourdan, Fred; Xu, Y.; Liu, L. (Elsevier BV, 2017)
We investigate the Mesozoic–Cenozoic thermal history of the Daxi region (central SE South China Block) to evaluate the influence of the subduction of the Paleo-Pacific oceanic plate beneath the SE South China Block along the block's southeast margin on the tectonothermal evolution of the upper plate. We apply a multi-chronological approach that includes U-Pb geochronology on zircon, 40Ar/39Ar dating on muscovite and biotite from granitic rocks as well as fission-track and (U-Th-Sm)/He analyses on zircon and apatite from granitic and sedimentary rocks. The Heping granite, located in the Daxi region, has a magmatic age of ca. 441 Ma. The biotite 40Ar/39Ar ages of ca. 193 Ma for the Early Jurassic Shibei granite and ca. 160 Ma for the Late Jurassic Fogang granite, respectively, reflect magmatic cooling. The Triassic Longyuanba granite yielded a muscovite 40Ar/39Ar age of ca. 167 Ma, recording heating to ≥ 350 °C induced by nearby intrusion of Middle Jurassic granites. Zircon fission-track and (U-Th-Sm)/He ages from Lower Carboniferous–Lower Jurassic sandstones (140–70 Ma) record continuous cooling during the Cretaceous that followed extensive Middle–Late Jurassic magmatism in the Daxi region. Cretaceous cooling is related to exhumation in an extensional tectonic setting, consistent with lithospheric rebound due to foundering and rollback of the subducted Paleo-Pacific oceanic plate. Apatite fission-track (53–42 Ma) and (U-Th-Sm)/He ages (43–36 Ma), and thermal modelling document rapid cooling in the Paleocene–Eocene, which temporally coincides with continental rifting in the SE South China Block in the leadup to the opening of the South China Sea.